NEW NORMAL AVIATION SAFETY: INTERNATIONAL REGULATIONS ON PREVENTION OF COVID-19 TRANSMISSION BY MEAN OF INTERNATIONAL AVIATION - Garry Gumelar Pratama (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
AbstractEach party of the Chicago Convention 1944, the treaty governing international aviation, has agreed to take effective measures to prevent the spreading of diseases including the New CoronaVirus 2019 or COVID-19, which ruptures so many aspects of life. In fact, the current situation is not the first encounter of international aviation law with the same problem, combating dangerous and contagious disease pandemic. Before COVID-19, International aviation had to deal with highly contagious diseases such as Avian Influenza and Severe Acute Respiratory Syndrome (SARS). Now, states have learned better to keep in close consultation with the organizations that adopt international regulations relating to sanitary measures applicable to aviation. Due to the great danger to humankind, cutting the spreading of communicable diseases on international flights is not a mere legal obligation but also a moral responsibility to the human race as a whole. Keywords: Air Law, COVID 19, International Aviation, International Regulations, New Normal AbstrakNegara pihak dalam Chicago Convention 1944 sebagai salah satu sumber hukum internasional yang mengatur penerbangan internasional telah berkomitmen untuk mencegah penyebaran penyakit melalui penerbangan, termasuk juga penyebaran Novel Coronavirus 2019 atau disingkat COVID-19. Pandemik yang telah meluluhlantakkan berbagai aspek kehidupan tersebut, sebenarnya bukan merupakan situasi pertama yang dihadapi oleh dunia penerbangan internasional, pada khususnya. Sebelum pandemik COVID-19, telah terdapat berbagai macam penyakit yang menyebar, salah satunya melalui penerbangan, termasuk Flu Burung (Avian Influenza) dan Severe Acute Respiratory Syndrome (SARS). Saat ini, dengan demikian, negara telah memiliki pengalaman untuk mengadakan koordinasi dengan lembaga-lembaga internasional terkait tindakan saniter yang dapat diaplikasikan pada perjalanan pesawat. Pemutusan penyebaran penyakit menular melalui penerbangan internasional merupakan masalah moral sekaligus masalah hukum. Kata Kunci: COVID-19, Hukum Udara, Penerbangan Internasional, Regulasi Internasional, Normal Baru